tana = 3/4 tan b = 2/7

We know that:

tan(a-b) = (tan a - tanb)/(1+ tana*tanb)

Let us substitute:

tan(a-b) = (3/4 - 2/7) / [1+ (3/4)*(2/7)]

= (21-8)/28 / (1+ 6/28)

= 13/28 / (34/28)

= 13/34

**==> tan(a-b) = 13/34**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now